Curriculum, identity(ies) and other stories: a look to the History of Africa and afro-descendants in Buenos Aires province context - Francisco Ramallo (Corporación Universitaria Minuto de Dios, 2017)
This article proposes to reflect about the reasons by which we believe that the history of Africa and the afrodescendants becomes important, especially in the teaching of History in the Argentinian high school. Our approach is framed within the analysis of new presences and absences of these cultures and towns in the curricular designs in the context of the Buenos Aires Province, given that in the last years attention was payed to the need of reviewing and renovating the school contents according to the demands of the contemporary society. There this other histories constituted as a new appearance and rupture in relation with the Eurocentered perspectives and contents that characterized the teaching of World History -no longer called Universal-. In the first place, after telling our tour of research, we establish the main aspects that characterize the approached curricular designs; subsequently, in the second stage, possible lines of work are established that contribute to overcome and critically review the African History and that of the afro-descendants in that normative and in the construction of a national identity.